Intracardiac 4D Flow MRI in Congenital Heart Disease: Recommendations on Behalf of the ISMRM Flow & Motion Study Group. Issue 3 (17th July 2019) - Zhong, Liang; Schrauben, Eric M.; Garcia, Julio; Uribe, Sergio; Grieve, Stuart M.; Elbaz, Mohammed S.M.; Barker, Alex J.; Geiger, Julia; Nordmeyer, Sarah; Marsden, Alison; Carlsson, Marcus; Tan, Ru‐San; et al.
Abstract : Level of Evidence: 5 Technical Efficacy: Stage 5 J. Magn. Reson. Imaging 2019;50:677–681.